Prognostic factors and follow‐up strategy for superficial soft‐tissue sarcomas: Analysis of 622 surgically treated patients from the scandinavian sarcoma group register. Issue 8 (3rd June 2015) - Tsagozis, Panagiotis; Bauer, Henrik C.; Styring, Emelie; Trovik, Clement S.; Zaikova, Olga; Brosjö, Otte
<x xml:space="preserve">Abstract</x> Background and Objectives Our study aimed to describe the clinical outcome of patients with superficial soft‐tissue sarcomas (SSTS), define prognostic factors and provide evidence for a rational surveillance scheme. Methods Data for 622 consecutive, surgically treated SSTS patients were retrieved from the Scandinavian Sarcoma Group Register. We assessed the rates of local recurrence (LR) and metastasis (M), as well as overall survival (OS), local recurrence free‐survival (LRFS) and metastasis‐free survival (MFS) of the cohort. Results The incidence of LR and M was 9% and 12%, respectively. OS at 5 years was 79%, LRFS was 74% and MFS 76%. Factors that affected OS, LRFS, and MFS were tumor size and patient age. Additionally, tumor grade was an independent prognostic factor for LRFS. The majority of LR and M events were observed the first 2 years of follow‐up. Clear surgical margins were correlated to lower risk for LR. Selected patients benefited from adjuvant radiotherapy. Conclusions SSTS have a favourable prognosis, which is mainly determined by tumour‐associated factors. Adequate surgical margins are important for local control, whereas radiotherapy has a secondary role. The data support current surveillance schemes, with a closer follow‐up the first 2 years after surgery. J. Surg. Oncol. 2015 111:951–956. © 2015 Wiley Periodicals, Inc.